Post-war medical policy (report) - Daily Herald ; Scottish Union of Bakers, Confectioners and Bakery Workers
1941-10-29 1941 1940s 6 pages ADMISSION OF THE SICK TO HOSPITALS Before the War certain Local Government officials had power to obtain beds in hospitals for those who were considered to be in need of them. Article 75 of the Public Assistance Order 1930 governed the position, the relevant part stated: "The admission of a person to the hospital as a patient shall be authorised in one of the following ways - (b) by an order signed by a relieving officer accompanied (except in a case of sudden or urgent necessity) by a certificate of a District Medical Officer or other qualified medical practitioner." The first edition of the Daily Telegraph 23rd February 1954 [sic] contained a report of a Coroner's inquest on Alfred James Jones aged 77 at St. Pancras. He had been admitted to hospital only the day before his death suffering from heart disease, tuberculosis, bronchitis, broken leg and senile changes. Giving evidence Dr. Ernest Morgan said he had tried hard to get him into hospital several times, but had been unsuccessful. Regarding a verdict of accidental death, the Coroner said there were about a dozen such cases each year in that part of London. He went on to say "Ideally anybody in a bad state of health ought to be able to get into the hospital, but people in the age group of this man find it difficult to do so, unless they need immediate surgical treatment." 292/842/2/122